Study of Antioxidant Activity of Iwel from Brown Rice Flour and Seaweed Flour - Khairul Amri; Nazaruddin Nazaruddin; Siska Cicilia (International Journal of Advance Tropical Food, 2020)
This study aims to determine the effect of the proportion of brown rice flour and seaweed flour on the antioxidant activity of iwel, a traditional Lombok cake. This study used a completely randomized design (CRD) with one factor, namely the proportion of brown rice flour and seaweed flour with 6 treatments, namely K0 (100%: 0%), K1 (90%: 10%), K2 (80%: 20) , K3 (70%: 30%), K4 (60%: 40%) and K5 (50%: 50%). Each treatment was repeated 3 times in order to obtain 18 experimental units. The chemical parameters observed included chemical parameters (antioxidant activity, moisture content, ash content), and organoleptic parameters (texture, color, taste and odor) by hedonic and scoring. Observation data were analyzed using Analysis of Variance at the 5% real level using Co-stat software. If there is a significant difference, a further test is carried out using Orthogonal Polynomials for chemical parameters and Honest Significant Difference (BNJ) at the 5% level for organoleptic parameters. The results showed that the higher the addition of seaweed flour caused a decreased in antioxidant activity, moisture content, and preference of panelists but increased ash content of iwel. The proportion of brown rice flour and seaweed flour at K2 was the best treatment seen from the antioxidant activity of 58.80%; moisture content 17.13%; and the ash content of 3.94% and the panelists prefer a bit chewy texture, red color, taste of brown rice flour and had not smell of seaweed.